Analysis of casing deformation with the effect of natural fracture nearby wellbore in the Sichuan Basin. (7th February 2022) - Zhang, Hui; Li, Jun; Zhang, Xin; Zhang, Xiaojun
Abstract: At present, the local natural fracture is an important cause of casing deformation in shale gas horizontal wells in the Sichuan Basin. But the relevant mechanism is not comprehensive, ignoring multi-scale characteristic of fractures, and no systemic solutions are proposed. Based on summary and analysis of casing deformation in the Sichuan Basin over the years, quantitative risk assessment approach (QRA) and finite element method were applied to research the effect of multi-scale nature fractures. Furthermore, we discussed the optimization of the fracturing construction parameters of shale gas horizontal wells according to different fracture scales. The results show the following. a) most of the deformed positions correspond to the fracture positions in the ant-tracking seismic volume and the micro-seismic signals. Moreover, deformation morphologies are in line with the characteristics of casing shear and extrusion deformation. b) Large-scale natural fractures (LNF) were prone to cause casing shear deformation; the casing at the micro-fracture networks was often extruded; multi-scale fractures induce remote micro-seismic distribution. c) we suggest that microfractures segments adopt multi-cluster and tighter clusters fracturing technologies, while LNF segments increase segments and clusters spacing. These methods were well applied in the field and the casing deformation rate was significantly reduced.